Association Between Body Composition and Pulmonary Function Tests Among Health Care Workers in Iran - Pouragha, Hamidreza; Kazemi, Hosein; Pouryaghoub, Gholamreza; Mehrdad, Ramin (Current Respiratory Medicine Reviews, 2021)
Background: Why is bodyweight not a predictor of lung function, while height, sex, race, and age are predictors of lung capacity and function? In this study, we want to investigate the association between body composition and pulmonary function. And, as much as possible, answer the question of why bodyweight is not predictive of lung function. Methods: This cross-sectional study was performed among 2967 employees of Tehran University of Medical Sciences (TUMS) who participated in the TUMS Employees Cohort (TEC) study. The body composition of the participants was measured using the Bioelectrical Impedance Analysis (BIA) method. Anthropometric variables were also measured as a confounder. The pulmonary function of participants was assessed by a forced spirometry test. Results: The correlation of BIA values including fat-free mass and total body water with a pulmonary function such as FEV1, FVC, and FEF25-75 is higher than most anthropometric values such as weight, wrist circumference, and the waist to hip ratio. Also, in regression analysis, age and sex had an association with pulmonary function, but the weight did not show a significant relationship. On the other hand, fat-free mass and visceral fat were significantly associated with pulmonary function. One is direct and the other is inverse. Conclusion: We observed a negative association between visceral fat and pulmonary function tests and a direct association between Fat-free mass pulmonary function tests (FEV1 and FVC) adjusted for age, sex, and anthropometric indices.
Keywords: health personnel